The MotherCare Guide To Healthy, Beauty And Exercise For Pregnancy And After - Morse, Elisabeth (Conran Octopus Limited, 1989)
This practical and beautifully illustrated book will show the reader ways to look after herself throughout her pregnancy and once her baby is born.
Keywords: Exercise; Health; Non Fiction; Pregnancy